2016
DOI: 10.1152/ajpregu.00188.2016
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of capacities for iron transport and sequestration reflects plasma volumes and heart mass among white-blooded notothenioid fishes

Abstract: The family Channichthyidae or “icefishes” (suborder Notothenioidei) represents the only vertebrates lacking hemoglobin (Hb) as adults. Several icefish species also do not express cardiac myoglobin (Mb). We address how levels of proteins involved in iron (Fe) processing (transport, sequestration, and export) vary among white- and red-blooded notothenioids, and whether absence of Hb and/or Mb in channichthyids is accompanied by expansion of contents of Fe-binding proteins to protect against unchaperoned Fe. Leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…The mechanism by which heme potentiates the formation of intracellular ROS is unclear, especially given that transcript levels of haptoglobin, ferritin, serotransferrin and hepcidin, which are involved in Fe transport and sequestration, are higher in the Antarctic fish Dissostichus mawsoni than in temperate species (Chen et al, 2008). Also, in our previous work, we found that tissue levels of the proteins ferritin and ceruloplasmin were generally higher in red-blooded species than in icefishes, although transferrin levels were no different among species (Kuhn et al 2016).…”
Section: Discussionmentioning
confidence: 73%
“…The mechanism by which heme potentiates the formation of intracellular ROS is unclear, especially given that transcript levels of haptoglobin, ferritin, serotransferrin and hepcidin, which are involved in Fe transport and sequestration, are higher in the Antarctic fish Dissostichus mawsoni than in temperate species (Chen et al, 2008). Also, in our previous work, we found that tissue levels of the proteins ferritin and ceruloplasmin were generally higher in red-blooded species than in icefishes, although transferrin levels were no different among species (Kuhn et al 2016).…”
Section: Discussionmentioning
confidence: 73%
“…Iron is found at the center of hemoglobin and myoglobin, which bind oxygen for vascular transport and storage, respectively (Beard et al, 1996). In vertebrates, as much as 80% of the total iron content can be bound within these two metalloproteins (Kuhn et al, 2016). Although rainbow trout have been shown to take up iron across their gills in ironrich freshwaters, this pathway requires very high dissolved iron concentrations (half-saturation constant of 21 nM) (Cooper and Bury, 2007) so that it should be negligible at the concentrations found in iron-poor seawater (less than 0.2 nM).…”
Section: Iron In Marine Fishmentioning
confidence: 99%
“…These extremely unusual features have been most often associated with the low temperatures and high dissolved oxygen concentrations of Antarctic waters, which could reduce the requirement for oxygen transportation and storage (Kock, 2005). However, the loss of hemoglobin is accompanied by dramatic adaptations to maintain sufficient oxygen supply to their tissues, including up to a five-fold increase in ventricle size and four-fold increase in total blood volume compared to red-blooded fish of similar size (Kuhn et al, 2016). Even the increased blood volumes cannot overcome what appear to be many profound disadvantages, and explaining why the absence of hemoglobin persists has been recognized as an evolutionary conundrum (Sidell and O'Brien, 2006), even cited as an example of a deleterious adaptation or "disaptation" (Garofalo et al, 2009).…”
Section: Possible Adaptations To Low Iron Availabilitymentioning
confidence: 99%
“…Indeed, without iron-binding hemoglobin, iron content in icefish blood plasma is less than 5% of closely related red-blooded species (di Prisco et al, 2002). Yet there is even further evidence of additional iron minimization beyond loss of hemoglobin and myoglobin: concentrations of non-heme iron in Antarctic icefish plasma are one-sixth of that in closely related red-blood species, and are lower by roughly half across various tissues (Kuhn et al, 2016). With a tissue level reduction in iron content, paired with the knockout of two primary iron binding proteins, the iron requirements of icefish normalized to biomass could be greater than 95% compared to other organisms and awaits confirmation.…”
Section: Discussionmentioning
confidence: 99%